A retrospective study of burden, pattern, and site of pediatric tuberculosis patients registered in the district tuberculosis center of Jabalpur district - Arvind Sharma; Sunita Patel; Prince Kumar Lodhi; Aprajita (Asian Journal of Medical Sciences, 2025)
Background: Tuberculosis (TB) is a major global public health threat and its impact on pediatric population is particularly concerning. India has the highest fraction of the world’s TB burden. TB is a disease with high morbidity and mortality. Aiming for eradication in 2025 announced by the honorable Prime Minister which is ahead for global eradication which is 2030. Aims and Objectives: This study aims to find out the burden, pattern, site, and outcomes in District TB Center (DTC), Jabalpur. Materials and Methods: It is a retrospective record-based study conducted in the DTC, Jabalpur, for 6 months (January 2024–June 2024) for the years 2021, 2022, and 2023 among 623 patients. Data were entered in MS Excel, and descriptive statistical analysis was done using IBM-Statistical Packages for the Social Sciences version 23.0. Results: The burden of pediatric patients in 2021, 2022, and 2023 was 2.91%, 4.43%, and 3.03%, respectively, among all TB patients. Among 623 patients, the mean age was 8.42±4.42 (M±SD) years. 346 (55.5%) were female and 277 (44.4%) were male. Overall, 368 (59%) were extrapulmonary cases and 255 (40.9%) patients of pulmonary TB. In treatment outcomes 451 (72.3%) were treatment completed, 67 (10.7%) cured, 59 (9.4%) died, 12 (1.9%) treatment ongoing, 3 (0.4%) treatment regimens changed, 1 (0.1%) treatment failure, and 18 (2.8%) were not evaluated. Conclusion: The pattern of pediatric TB increased and then slightly decreased in 3 years. Among extrapulmonary patients, majority were of lymph node TB, followed by meningitis, abdominal, pleural, bone, and spinal; maximum cases classified as others which were not specified.